2015
DOI: 10.1111/nmo.12654
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of colon and bladder crosstalk in an experimental colitis model using contrast‐enhanced magnetic resonance imaging

Abstract: Background Inflammatory bowel disease (IBD) consists of two chronic remitting-relapsing inflammatory disorders in the colon referred to as ulcerative colitis (UC) and Crohn’s disease (CD). IBD affects about 1.4 million Americans. TNBS (2,4,6-trinitrobenzene sulfonic acid)-induced colitis is a widely used model of experimental intestinal inflammation with characteristic transmural and segmental lesions that are similar to CD. Methods Here we report on the use of contrast-enhanced MRI (CE-MRI) to monitor in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Many previous studies have shown that the permeability of the bladder epithelium increases significantly after colon inflammation. 41 , 42 Mast cell activation has been proved to be a key factor, and mast cell stabilizers can reverse the increase in epithelial permeability. 22 The permeability change of the urothelium is an important cause of bladder pain and urination symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have shown that the permeability of the bladder epithelium increases significantly after colon inflammation. 41 , 42 Mast cell activation has been proved to be a key factor, and mast cell stabilizers can reverse the increase in epithelial permeability. 22 The permeability change of the urothelium is an important cause of bladder pain and urination symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Two animal models were used. A rat model described in detail previously 25,[42][43][44][45] was used to confirm that the SuperGAG restores impermeability using the TEER "gold standard." This same model was used to confirm that restoring bladder impermeability abrogates the abdominal pain result.…”
Section: Animal Model Methodsmentioning
confidence: 99%
“…Two animal models were used. A rat model described in detail previously 25,42‐45 was used to confirm that the SuperGAG restores impermeability using the TEER “gold standard.” This same model was used to confirm that restoring bladder impermeability abrogates the abdominal pain result. The restoration of impermeability also was confirmed in a transgenic mouse model that is receiving increasing acceptance as a model for IC/BPS 46 .…”
Section: Methodsmentioning
confidence: 99%
“…Gd-DTPA normally does not go through an impermeable bladder wall. Of interest, we were also able to detect bladder-colon crosstalk associated colitis via intravenous (iv) administration of Gd-DTPA [ 28 ], as well as BWH from colon-bladder crosstalk following the induction of intestinal cystitis with trinitrobenzene sulfonic acid (TNBS) [ 38 ]. CE-MRI of BWH could therefore also be applied to assess colon–bladder crosstalk in inflammatory bowel disease (IBD) patients, as well as other inflammatory colon diseases.…”
Section: Mri Imagingmentioning
confidence: 99%
“…Following the preclinical rat PS-induced BWH study, we then conducted a human pilot study comparing IC/BPS patients with normal individuals and clearly demonstrated the clinical feasibility of detecting BWH in IC/BPS [ 41 ]. Due to the increased thickness of the human bladder wall, BWH was detected within the bladder wall (see Figure 1 G–I where there was a significant increase in % difference in MRI SI for the IC bladders ( p < 0.001) compared to controls) [ 41 ] rather than the outside regions as seen in the preclinical models [ 28 , 38 , 39 ]. Another group used a mixture of both Gd-DTPA (Gadavist) and an iron oxide contrast agent, ferumoxytol, to further enhance bladder wall contrast in rats with induced cystitis (PS-induced) [ 42 ] and more recently in patients with IC [ 43 ].…”
Section: Mri Imagingmentioning
confidence: 99%